Thrust distribution for 3-jet production from e+e− annihilation within the QCD conformal window and in QED - Leonardo Di Giustino (Elsevier, 2021)
We investigate the theoretical predictions for thrust distribution in the electron positron annihilation to three-jets process at NNLO for different values of the number of flavors, Nf. To determine the distribution along the entire renormalization group flow from the highest energies to zero energy we consider the number of flavors near the upper boundary of the conformal window. In this regime of number of flavors the theory develops a perturbative infrared interacting fixed point. We then consider also the QED thrust obtained as the limit Nc→0 of the number of colors. In this case the low energy limit is governed by an infrared free theory. Using these quantum field theories limits as theoretical laboratories we arrive at an interesting comparison between the Conventional Scale Setting - (CSS) and the Principle of Maximum Conformality (PMC∞) methods. We show that within the perturbative regime of the conformal window and also out of the conformal window the PMC∞ leads to a higher precision, and that reducing the number of flavors, from the upper boundary to the lower boundary, through the phase transition the curves given by the PMC∞ method preserve with continuity the position of the peak, showing perfect agreement with the experimental data already at NNLO.